2017
DOI: 10.1103/physrevb.95.184501
|View full text |Cite
|
Sign up to set email alerts
|

Nodeless superconductivity and the peak effect in the quasiskutterudites Lu3Os4Ge13 and Y3Ru<

Abstract: We report an investigation of the superconducting states of Lu 3 Os 4 Ge 13 and Y 3 Ru 4 Ge 13 single crystals by measurements of the electrical resistivity, ac susceptibility and London penetration depth. The analysis of the penetration depth and the derived superfluid density indicates the presence of nodeless superconductivity and suggest that there are multiple superconducting gaps in both materials. Furthermore, ac susceptibility measurements of both compounds display the peak effect in the low temperatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
6
4
0
Order By: Relevance
“…Considering that we find the 1/1 superlattice to be metallic, a more systematic study comparing the properties of bulk solid solutions with short-period superlattices of similar composition would be instructive. Note that DFT+U calculations for magnetically ordered LaVO 3 /LaTiO 3 superlattices also found the 1/1 case with layering perpendicular to [001] to be metallic, in agreement with our DFT+DMFT results, while other stacking directions turned out to be insulating [29]. Another study addressed the role of strain and polarity at interfaces of LaVO 3 and LaTiO 3 with various substrates [30], and suggested that the insulator-to-metal transition in both materials is due to a complex interplay of structural, and electronic degrees of freedom that affects the two materials in different ways.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Considering that we find the 1/1 superlattice to be metallic, a more systematic study comparing the properties of bulk solid solutions with short-period superlattices of similar composition would be instructive. Note that DFT+U calculations for magnetically ordered LaVO 3 /LaTiO 3 superlattices also found the 1/1 case with layering perpendicular to [001] to be metallic, in agreement with our DFT+DMFT results, while other stacking directions turned out to be insulating [29]. Another study addressed the role of strain and polarity at interfaces of LaVO 3 and LaTiO 3 with various substrates [30], and suggested that the insulator-to-metal transition in both materials is due to a complex interplay of structural, and electronic degrees of freedom that affects the two materials in different ways.…”
Section: Discussionsupporting
confidence: 88%
“…However, our calculations show that for all considered multilayers the charge transfer at the LaVO 3 /LaTiO 3 interface is in the opposite direction, i.e., charge is transferred from the Ti cations in LaTiO 3 to the V cations in LaVO 3 , thereby increasing the charge imbalance of the d states at the interface. This is also in qualitative agreement with recent DFT+U calculations for magnetically ordered LaVO 3 /LaTiO 3 superlattices [29]. Furthermore, the charge transfer is strongly localized at the interface, converging back to bulk-like occupations within only three layers.…”
Section: B Charge Transfersupporting
confidence: 91%
“…Zero-field (ZF) muon spin relaxation measurements reveal a significant variation of the relaxation rate with temperature and, thus, the presence of spontaneous magnetic fields, breaking time-reversal symmetry in the superconducting state. Furthermore, transverse-field (TF) measurements of Lu 3 Os 4 Ge 13 provide the temperature dependence of the superconducting contribution to the relaxation rate, σ sc , which-in accordance with the previous reports [20,21]-is consistent with a multi-gap state with significantly different gap magnitude on different Fermi sheets. We find comparatively small values of ∆ i (T = 0)/k B T c for the two superconducting gaps, ∆ i , indicative of weakly coupled superconductivity in Lu 3 Os 4 Ge 13 .…”
Section: Introductionsupporting
confidence: 89%
“…Two initial studies of Lu 3 Os 4 Ge 13 by Prakash et al revealed two-gap bulk superconductivity from lowtemperature electronic specific heat measurements and a non-linear dependence of the Sommerfeld coefficient, γ n , under magnetic field [19,20]. The superfluid density measurements via tunnel diode oscillator (TDO) also confirmed the two-gap nature of the superconducting state [21]. Another noteworthy property of Lu 3 Os 4 Ge 13 is the high value of the upper critical field, H c2 , which is close to its Pauli limiting value [22], and the high transition temperature T c for a relatively low carrier density system.…”
Section: Introductionmentioning
confidence: 96%
“…(c) Magnetization data of the borocarbide superconductor YNi 2 B 2 C exhibiting a characteristic peak near H c2 [123]. (d) Magnetic susceptibility curves with minima associated with the PE, with the irreversibility between the heating and cooling curves shown inset [124]. (e) Peaks seen in the magneto-caloric effect of a Nb sample [110].…”
Section: Introductionmentioning
confidence: 99%